2018
DOI: 10.3389/fmicb.2018.01339
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular Mycorrhizal Symbiosis Leads to Differential Regulation of Drought-Responsive Genes in Tissue-Specific Root Cells of Common Bean

Abstract: Arbuscular mycorrhizal fungi (AMF) colonization in plants promotes both local and systemic changes in the gene expression profiles of the host that might be relevant for drought-stress perception and response. Drought-tolerant common bean plants (cv. BAT 477), colonized by a mixture of AMF (Glomus clarum, Acaulospora scrobiculata, and Gigaspora rosea), were exposed to a water deprivation regime of 96 h during pre-flowering. Root transcriptomes were accessed through RNA-Seq revealing a set of 9,965 transcripts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 123 publications
0
30
0
1
Order By: Relevance
“…Downregulation of genes TIP1;1, TIP2;3, PIP1;1, PIP1;3, PIP1;4, PIP1;6, PIP2;2, and PIP2;4 whereas only upregulation of TIP4;1 were observed in drought-sensitive cultivar colonized by Rhizophagus irregularis, supporting the decrease in water loss in host plants subjected to drought stress [71]. Recent research also revealed a significant shift in the transcriptional regulation profiles with AQP genes as potential targets in mycorrhizal roots, in comparison to non-AM ones during a water stress event, which may influence some key metabolic pathways linked with drought response [76]. In parallel, it has been proposed that during drought stress a controlled mechanism mediated by the presence of arbuscules at cortical cells in roots fine-tuned the gene expression regulation in the host plant [76].…”
Section: Amf-induced Changes In Expression Of Aquaporin Genes Transcmentioning
confidence: 68%
See 1 more Smart Citation
“…Downregulation of genes TIP1;1, TIP2;3, PIP1;1, PIP1;3, PIP1;4, PIP1;6, PIP2;2, and PIP2;4 whereas only upregulation of TIP4;1 were observed in drought-sensitive cultivar colonized by Rhizophagus irregularis, supporting the decrease in water loss in host plants subjected to drought stress [71]. Recent research also revealed a significant shift in the transcriptional regulation profiles with AQP genes as potential targets in mycorrhizal roots, in comparison to non-AM ones during a water stress event, which may influence some key metabolic pathways linked with drought response [76]. In parallel, it has been proposed that during drought stress a controlled mechanism mediated by the presence of arbuscules at cortical cells in roots fine-tuned the gene expression regulation in the host plant [76].…”
Section: Amf-induced Changes In Expression Of Aquaporin Genes Transcmentioning
confidence: 68%
“…Recent research also revealed a significant shift in the transcriptional regulation profiles with AQP genes as potential targets in mycorrhizal roots, in comparison to non-AM ones during a water stress event, which may influence some key metabolic pathways linked with drought response [76]. In parallel, it has been proposed that during drought stress a controlled mechanism mediated by the presence of arbuscules at cortical cells in roots fine-tuned the gene expression regulation in the host plant [76].…”
Section: Amf-induced Changes In Expression Of Aquaporin Genes Transcmentioning
confidence: 99%
“…(). Similarly, transcriptomic studies of genes up‐regulated in response to AM colonization find some MycEx genes, but no family is over‐represented (Sugimura & Saito, ; Recchia et al., ; Vangelisti et al., ; and Supporting Information Table ). Transcriptomic studies do report up‐regulation of defense‐related genes following AM colonization, but these genes are mostly downstream of the signaling pathways represented by the MycEx familes (Calabrese et al., ; Hohnjec, Vieweg, Puhler, Becker, & Kuster, ).…”
Section: Discussionmentioning
confidence: 92%
“…They found 744 genes up‐regulated in the AM‐treated plants. Recchia, Konzen, Cassieri, Caldas, and Tsai () used RNA‐seq to compare root transcriptomes of Phaseolus vulgaris plants grown with or without AM fungal inoculum. They found 714 genes up‐regulated in the plants grown with AM.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation